Ecological state of water objects of Poltava region - Фесенко, О. Г.; Коваль, В. В.; Кучерявий, С. О. (Scientific Progress & Innovations, 2015)
The results of research on content of pesticides, heavy metals and nitrates, in superficial and underground waters of Poltava region are presented. Researches were conducted in 2013–2014 on the base of Poltava branch of public institution «Institute of guard of soils of Ukraine». It is certain that the wide use of facilities of plants’ defence in agriculture can be a reason of contamination of environment by them, in particular water objects. We got results that testify the significant piling up of nitrates, heavy metals and absence of remaining amounts of pesticides.